2011
DOI: 10.1371/journal.pone.0028514
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Is Part of Human Trophoblast Invasion Machinery - A Functional Study In Vitro

Abstract: BackgroundInteractions of glycoconjugates with endogenous galectins, have been long proposed to participate in several reproductive processes including implantation. In human placenta gal-1, gal-3, gal-8, and gal-13 proteins are known to be present. Each of them has been proposed to play multiple functions, but so far no clear picture has emerged. We hypothesized that gal-1 participates in trophoblast invasion, and conducted Matrigel invasion assay using isolated cytotrophoblast from first trimester placenta a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 71 publications
4
70
0
5
Order By: Relevance
“…In this context, gal-1 is expressed in the CTB of middle and distal cell columns differentiating toward fully invasive trophoblast (Vicovac et al, 1998) and has been recently reported as a component of the human trophoblast invasion machinery. Thus, while gal-1 silencing has a negative effect on trophoblast cell invasion capacity, exogenous gal-1 stimulation has been shown to enhance this process (Kolundzic et al, 2011). This observation is in agreement with the identification of gal-1 expression as a signature of cell invasiveness when comparing highly and poorly invasive mammary carcinoma cell lines (Harvey et al, 2001).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this context, gal-1 is expressed in the CTB of middle and distal cell columns differentiating toward fully invasive trophoblast (Vicovac et al, 1998) and has been recently reported as a component of the human trophoblast invasion machinery. Thus, while gal-1 silencing has a negative effect on trophoblast cell invasion capacity, exogenous gal-1 stimulation has been shown to enhance this process (Kolundzic et al, 2011). This observation is in agreement with the identification of gal-1 expression as a signature of cell invasiveness when comparing highly and poorly invasive mammary carcinoma cell lines (Harvey et al, 2001).…”
Section: Discussionsupporting
confidence: 79%
“…Gal-1 is up-regulated within the decidua (on stromal cells and NK cells) and can induce tolerogenic DCs, emerging as a key modulator of T cell functions (Blois et al, 2007;Kopcow et al, 2008;Than et al, 2008). In addition, gal-1 has been found to induce trophoblast invasion and fusion during placentation, and may thus be important for the regulation of trophoblast differentiation (Fischer et al, 2010;Kolundzic et al, 2011). Together with its influence on the immune evasion machinery in trophoblast cells by regulating HLA-G expression described here, these data strongly suggest that gal-1 plays a central role in the maintenance of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that both gals (Than et al, 2012; and EVs (Redman and Sargent, 2008;Mincheva-Nilsson and Baranov, 2014) serve as important mediators in early pregnancy events. It is of interest to note that EVT cell invasion is increased by both gal-1 (Kolundzic et al, 2011b) and EVs from cytotrophoblast cells grown in a hypoxic environment (Salomon et al, 2013). Both gal-1 (Blois et al, 2007;Tirado-Gonzalez et al, 2013) and placental EVs (Stenqvist et al, 2013;Mincheva-Nilsson and Baranov, 2014;Tannetta et al, 2014) are involved in immunoregulation during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Three members of the galectin family are found in extravillous trophoblast (EVT): gal-1, gal-3 (Maquoi et al, 1997;Vićovac et al, 1998), and gal-8 (Kolundzic et al, 2011a). In EVT, gals may play multiple roles, possibly in cell adhesion and migration, as shown for gal-1 in EVT in vitro (Kolundzic et al, 2011b). Gal-1 has been also associated with different pregnancy disorders such as spontaneous abortion (Ramhorst et al, 2012), preeclampsia (Than et al, 2008), and gestational diabetes mellitus .…”
Section: Introductionmentioning
confidence: 99%